Mechanisms of Kaempferol in the treatment of diabetes: A comprehensive and latest review - Yang, Yan; Chen, Zhengtao; Zhao, Xiaoyan; Xie, Hongyan; Du, Lian; Gao, Hong; Xie, Chunguang (Frontiers in Endocrinology, 2022)
“Obesity-insulin resistance-β cells apoptosis” is an important trilogy of the pathogenesis of type 2 diabetes. With the global pandemic of obesity and diabetes, continuous research and development of new drugs to prevent and block the pathological progress is the focus of drug research and development. According to recent research, natural product kaempferol has excellent anti diabetes effect. Therefore, this paper comprehensively summarizes the frontier research and pharmacological mechanism of kaempferol anti diabetes. The successful research and development of kaempferol may yield a significant leap in the treatment of diabetesand diabetes complications.